Synthesis of azo polymers by etheric derivatives polymerization of allyl bromide and studying their bandgap and determine some of their properties - Jawish, Ghazi Mahmoud Hasso; Madwar, Rushdi; Kara Bet, Francois (Journal of natural sciences, life and applied sciences, 2021)
In this research, two ether derivatives of phenolic azo dyes were synthesized via Williamson’s reaction according to the SN2 mechanism. The prepared compounds were radically polymerized using (AIBN) as an initiator and their structures were identified by FT-IR and 1H-NMR. Furthermore, thermal properties of these polymers was made by (DSC). Bandgap energy have been calculated to indicate the ability of these polymers as optical semiconductors, it was 2.8ev, 2.4ev for P(AO2) and P(AON1) respectively. Beside the determination of refractive index, kinematic viscosity, density, and degree of Turbidity.